Negócios processuais e seus limites a partir da teoria liberal dos direitos fundamentais - Ribeiro, Luiz Filipe de Araújo (2017)
The present study analyzes the procedural agreement and their limits from the point of view of a liberal theory of fundamental rights. Using the indirect documentation technique through bibliographic research, it initially presents the origin and historic evolution of procedural agreement abroad and in our legal order. Concepts and classifications of procedural agreement are also presented under the optics of several authors. It analyzes the hypotheses on procedural agreement brought by the articles 190, 191, 357, and 471 of the Code of Civil Procedure of 2015 (CPC/2015), without pretensions of exhausting the matter, but as a way to bring up the main criticism made by the doctrine up the present moment. It uses the juridical fact theory in order to analyze the existence requirements, validity, and effectiveness of contract procedures, seeking to comprehend the criteria used by the doctrine to delineate the limits for the celebration of contract procedures. Finally, using elements of legal dogmatics, is possible to identify: a fundamental rights protection area (freedom by the parts in the process); a state intervention in this protection area (article 190 of CPC/2015), in order to find constitutional justification for such intervention, to get, after all, to the conclusion about its (in)constitutionality.